The Gap Between Cybersecurity Experience and Behavior: A Case Study of Digital Native Students at the University of Papua - Numberi, Camelia Lusandri; Malino, Marlina; Nua, Redemptus Numba Nitu; Sumari, Jenita (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The purpose of this study is to analyze the influence of awareness, knowledge, experience, and compliance on students' digital security behavior at the University of Papua, in the context of social media use. This study conceptualizes digital security behavior as a behavioral phenomenon shaped by psychological factors and social norms within the Theory of Reasoned Action. A quantitative approach with a survey method was employed. Data were collected through a structured questionnaire distributed to active students who regularly use social media and were analyzed using multiple linear regression. The research instrument was developed based on indicators validated in previous studies and was subjected to validity and reliability testing before the primary analysis. The findings indicate that awareness, knowledge, and compliance have a positive and significant effect on students’ digital security behavior, whereas experience does not. These results reinforce the relevance of the Theory of Reasoned Action, particularly the role of attitudes and subjective norms in shaping digital security actions. Although students exhibit a relatively high level of awareness, gaps remain in terms of applied knowledge and practical skills. This study offers important implications for the development of digital security literacy in higher education institutions. Universities are encouraged to design practice-oriented, norm-based educational interventions and to integrate digital security into curricula and systematic training programs to foster sustainable digital security behavior among students.